Continua and disruptions in two Late Victorian episodes of female intimacy - Díaz Lage, José María (Victorians, 2021)
Both Thomas Hardy’s Desperate Remedies (1871) and George Gissing’s Demos (1886) contain episodes which current criticism frequently reads as lesbian, but which do not seem to have been taken as such when the novels were first published. They were, however, remarked upon as extravagant and vague, occupying a peculiar place in the action. This paper analyzes the relationships between women depicted in these episodes, not by ascertaining whether or not they are homosexual but by highlighting the ways in which they are necessarily unstable, in terms of discourse, of class conflicts, and of diegesis.
Keywords: George Gissing; Thomas Hardy; gender roles; class relationships; Scopus